PCR assays in detecting methicillin resistance in staphylococci: Coagulase negative staphylococci (CNS), S. aureus, and MRSA with the PVL gene - Merlino, J.; Kay, I.; Coombs, Geoffrey; Palladino, S. (Springer Netherlands, 2010)
Methicillin resistance, in particular hetero-methicillin resistance, in S aureus and the coagulase negative staphylococci (CNS) can be difficult to detect by phenotypic methods. Subsequently detection of the mecA gene for determining methicillin resistance in staphylococci is generally considered to be the Gold Standard. In Australian diagnostic microbiology laboratories, molecular assays used for the detection of the mecA gene have generally been designed in-house. These assays have either been single primer PCR assays targeting the mecA gene or a duplex primer PCR assay with primers targeting the mecA gene and a gene specific for S. aureus such as the nuc (nuclease) or fem gene. In some laboratories a Panton Valentine-leukocidin (PVL) gene primer has been incorporated with the duplex PCR assay allowing the detection of PVL virulence genes in S aureus. © 2010 Springer Science+Business Media B.V.